The impact of digital intelligence technologies on innovation performance: Evidence from specialized, refined, differential and innovative enterprises - Tian Zhao; Fa Zhang; Guoliang Zhuo; Qingqing Zhang; Qingwen Yuan (PLoS ONE, 2026)
The integration of digital and intelligent technologies has created new opportunities for the innovative growth of Specialized, Refined, Differential, and Innovative (SRDI) enterprises in China. This study examines SRDI enterprises listed on the Shanghai/Shenzhen A-share from 2014 to 2022. A three-stage Data Envelopment Analysis, incorporating a knowledge breadth framework, is employed to evaluate their innovation performance. Furthermore, an empirical analysis is conducted to assess the influence of digital intelligence on innovation outcomes. The results indicate that: (1) Digital intelligence, measured by datafication, digitization, and the adoption of intelligent technologies, significantly improves the innovation performance of SRDI enterprises, with intelligent technologies exerting the greatest effect; (2) Digital intelligence effectively mitigates financing constraints, allowing firms to allocate more resources to innovation; and (3) Heterogeneity analysis shows that the positive impact of digital intelligence is more pronounced among non-state-owned enterprises, manufacturing firms, and those located in Eastern China. These findings provides valuable guidance for policymakers seeking to develop targeted and differentiated strategies to enhance the innovation capacity of SRDI enterprises. In particular, the results underscore the role of digital intelligence in easing financing constraints. By accounting for firm-level heterogeneity, this study offers a robust theoretical and empirical foundation for policy design and delivers actionable recommendations for enterprises aiming to optimize resource allocation and strengthen innovation capabilities through digital transformation.